Dyspnea and Exercise Limitation in Mild COPD: The Value of CPET - James, Matthew D.; Milne, Kathryn M.; Phillips, Devin B.; Neder, J. Alberto; O'Donnell, Denis E. (Frontiers in Medicine, 2020)
The majority of smokers with chronic obstructive pulmonary disease (COPD) have mild airflow limitation as determined by simple spirometry. Although small airway dysfunction is the hallmark of COPD, many studies attest to complex heterogeneous physiological impairments beyond increased airway resistance. These impairments are related to inflammation of lung parenchyma and its microvasculature, which is obscured by simple spirometry. Recent studies using advanced radiological imaging have highlighted significant structural abnormalities in smokers with relatively preserved spirometry. These important studies have generated considerable interest and have reinforced the pressing need to better understand the physiological consequences of various morphological abnormalities, and their impact on the clinical outcomes and natural history of COPD. The overarching objective of this review is to provide a concise overview of the importance and utility of cardiopulmonary exercise testing (CPET) in clinical and research settings. CPET uniquely allows evaluation of integrated abnormalities of the respiratory, cardio-circulatory, metabolic, peripheral muscle and neurosensory systems during increases in physiologic stress. This brief review examines the results of recent studies in mild COPD that have uncovered consistent derangements in pulmonary gas exchange and development of “restrictive” dynamic mechanics that together contribute to exercise intolerance. We examine the evidence that compensatory increases in inspiratory neural drive from respiratory control centers are required during exercise in mild COPD to maintain ventilation commensurate with increasing metabolic demand. The ultimate clinical consequences of this high inspiratory neural drive are earlier onset of critical respiratory mechanical constraints and increased perceived respiratory discomfort at relatively low exercise intensities.